2023
DOI: 10.3389/fendo.2023.1145533
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in human sperm selection for assisted reproduction

Abstract: Male infertility is a commonly encountered pathology that is estimated to be a contributory factor in approximately 50% of couples seeking recourse to assisted reproductive technologies. Upon clinical presentation, such males are commonly subjected to conventional diagnostic andrological practices that rely on descriptive criteria to define their fertility based on the number of morphologically normal, motile spermatozoa encountered within their ejaculate. Despite the virtual ubiquitous adoption of such diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 208 publications
0
7
0
Order By: Relevance
“…Other advanced methods of sperm selection include intracytoplasmic morphologically selected sperm injection, magnetic-activated cell sorting, and zeta potential sperm selection. Recent analyses have found that there is insufficient evidence to determine whether these techniques lead to better clinical outcomes, such as higher live birth rates [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other advanced methods of sperm selection include intracytoplasmic morphologically selected sperm injection, magnetic-activated cell sorting, and zeta potential sperm selection. Recent analyses have found that there is insufficient evidence to determine whether these techniques lead to better clinical outcomes, such as higher live birth rates [ 7 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no additional recognized risks associated with PICSI, either for individuals who undergo fertility treatment or for children born through such treatment [ 6 ]. Hyaluronic acid (HA) receptors on plasma membranes are a maturation marker, and sperm that can bind immobilized HA in vitro are of higher quality [ 7 ]. The sperm selection process using the HA binding system can be applied in a laboratory setting and imitate the natural selection of male gametes cost-effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Fish sperm head plasma membranes have been demonstrated to contain syndecan (transmembrane heparan sulfate proteoglycan), which may play a role in fertilization [ 145 ]. Thus, HS may be on the sperm plasma membrane and released during transit along the epididymis, where sperm protein loss is substantially more predominant than sperm protein gain [ 146 , 147 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infertility affects up to 15% of couples who are of reproductive age, making it a somewhat prevalent condition. Around 30 % of partners who struggle to conceive are thought to be totally at blame, and male factors are also known to play a role in about 50% of all cases of infertility (Nixon et al, 2023). The standard examination of sperm does not accurately predict fertility; it is merely one of many variables.…”
Section: Introductionmentioning
confidence: 99%